High-strength Mg95Y3Zn1Ni1 alloy with LPSO structure processed by hot rolling. Issue 1 (2nd January 2017) - Liu, Wei; Zhang, Jinshan; Zhang, Zhifu; Wang, Dandan; Xu, Chunxiang; Zong, Ximei; Nie, Kaibo
ABSTRACT: Microstructures and mechanical properties of Mg95 Y3 Zn1 Ni1 alloy containing long period stacking ordered (LPSO) phase processed by hot rolling were systematically investigated in the present work. The results showed that the as-cast alloy was mainly composed of α-Mg and network 18 R LPSO phase. The thermal stability of 18 R LPSO phase in the as-cast alloys decreased with the decrease of Ni content. After solution treatment at 773 K for 40 h, network 18 R phase at grain boundary dissolved, while fine lamellar phase identified as 14H LPSO precipitated in the interior of grains. When the solid-solution alloy was hot rolled at 723 K with six passes and thickness reduction of 62%, some LPSO phases broke down and kinking of varying degrees occurred in LPSO phase. Meanwhile, the as-rolled α-Mg and LPSO phase redistributed aligned along the rolling orientation. The alloy exhibited excellent mechanical properties: yield strength of 282 MPa, ultimate tensile strength of 383 MPa, and elongation to failure of 16% at ambient temperature along the rolling orientation. The remarkable improvement of strength was ascribed to the refined microstructure induced by the deformation kinking and the crush of LPSO phase.